Ribosomal RNA mutations to rifampicin resistance - Macheke, Rulane Glenda (My University, 2012)
In prokaryotes, transcription and translation are coupled and as a result, the beginning of the messenger RNA is translated by the ribosome while the 3' end is still synthesized. How exactly this occurs is still not clear. One possibility is that RNA polymerase and the ribosomes may be in physical contact with each other at some stage during gene expression or RNA polymerase has a binding site in the ribosomes. Mutational analysis is one method to explore how coordination between these two moieties occurs in bacteria. An Escherichia coli strain with all seven chromosomal ribosomal RNA operons deleted, replaced by a single rrnB plasmid-borne operon, was used to isolate ribosomal RNA mutants with increased rifampicin resistance, two of which were studied further. The altered rrnB operon in pGM1 was obtained by spontaneous whilst in pGM2 by EMS mutagenesis. The mutated rrnB operon in pGM1 conferred resistance to 25μg/ml of rifampicin while in pGM2 resistance of 30μg/ml was observed. A base substitution of T to A at position 355 of the 23S rRNA was detected in pGM1and no nucleotide change was detected in pGM2. The successful isolation of ribosomal RNA mutants with rifampicin resistance is consistent with the hypothesis of interaction between the RNA polymerase and the ribosomes and suggests the part of this interaction is with the large ribosomal subunit.
MSc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: RNA; Ribosomes